Treatment Combinations with DNA Vaccines for the Treatment of Metastatic Castration-Resistant Prostate Cancer (mCRPC) - Gamat-Huber, Melissa (Cancers (Basel), 2020)
SIMPLE SUMMARY: The only vaccine approved by FDA as a treatment for cancer is sipuleucel-T, a therapy for patients with metastatic castration-resistant prostate cancer (mCRPC). Most investigators studying anti-tumor vaccines believe they will be most effective as parts of combination therapies, rather than used alone. Unfortunately, the cost and complexity of sipuleucel-T makes it difficult to feasibly be used in combination with many other agents. In this review article we discuss the use of DNA vaccines as a simpler vaccine approach that has demonstrated efficacy in several animal species. We discuss the use of DNA vaccines in combination with traditional treatments for mCRPC, and other immune-modulating treatments, in preclinical and early clinical trials for patients with mCRPC. ABSTRACT: Metastatic castration-resistant prostate cancer (mCRPC) is a challenging disease to treat, with poor outcomes for patients. One antitumor vaccine, sipuleucel-T, has been approved as a treatment for mCRPC. DNA vaccines are another form of immunotherapy under investigation. DNA immunizations elicit antigen-specific T cells that cause tumor cell lysis, which should translate to meaningful clinical responses. They are easily amenable to design alterations, scalable for large-scale manufacturing, and thermo-stable for easy transport and distribution. Hence, they offer advantages over other vaccine formulations. However, clinical trials with DNA vaccines as a monotherapy have shown only modest clinical effects against tumors. Standard therapies for CRPC including androgen-targeted therapies, radiation therapy and chemotherapy all have immunomodulatory effects, which combined with immunotherapies such as DNA vaccines, could potentially improve treatment. In addition, many investigational drugs are being developed which can augment antitumor immunity, and together with DNA vaccines can further enhance antitumor responses in preclinical models. We reviewed the literature available prior to July 2020 exploring the use of DNA vaccines in the treatment of prostate cancer. We also examined various approved and experimental therapies that could be combined with DNA vaccines to potentially improve their antitumor efficacy as treatments for mCRPC.